A interdisciplinaridade como perspectiva curricular em um objeto do programa do observatório da educação - CAPES no Amazonas - Segura, Eduardo Alberto das Chagas (2012)
Research dealing with curriculum development from the Interdisciplinary between mathematics, Portuguese and Natural Sciences. Analyzes the effects of the first year of a project linked to the Programme of the Centre for Education / Capes / UEA, executed in a public school in the city of Manaus, in the search for evidence of interdisciplinary perspectives. In the first chapter curriculum development and interdisciplinary expose the necessary theoretical basis to support the thesis. In the second chapter dealt with the investigative course, contextualizing the events of the first year of the Project of the Centre for Education. The third chapter presents the subjects investigated by using a questionnaire and individual interviews. We come to the conclusion that there is openness, at school, to new teaching strategies, in which interdisciplinarity can be a possibility